Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Some time ago I came across to the following integral:

$$I=\int_{0}^{1}\frac{1-x}{1+x}\frac{\mathrm dx}{\ln x}$$ What are the hints on how to compute this integral?

share|cite|improve this question
What happens if you substitute $u=\ln x$? (On second thought, it doesn't look too useful.) – Harald Hanche-Olsen Jan 16 '13 at 15:30
@HaraldHanche-Olsen: Isn't it an improper integral? – Babak S. Jan 16 '13 at 15:39
Fwiw Wolfram alpha couldn't find an indefinite integral, although it can find the definite integral, presumably by approximation. – JSchlather Jan 16 '13 at 15:40
@JacobSchlather: But it converges. – Babak S. Jan 16 '13 at 15:40
Maple says the value is $-\ln(\pi/2)$. – Harald Hanche-Olsen Jan 16 '13 at 15:42
up vote 20 down vote accepted

Make the substitution $x=e^{-y}$ and do a little algebra to get the value of the integral to be

$$\int_0^{\infty} \frac{dy}{y} \frac{e^{-y} - e^{-2 y}}{1+e^{-y}} $$

Now Taylor expand the denominator and get

$$\int_0^{\infty} \frac{dy}{y} (e^{-y} - e^{-2 y}) \sum_{k=0}^{\infty} (-1)^k e^{-k y} $$

If we can reverse the order of sum and integral, we get

$$ \sum_{k=0}^{\infty} (-1)^k \int_0^{\infty} \frac{dy}{y} (e^{-(k+1) y} - e^{-(k+2) y}) $$

The integral inside may be evaluated exactly, and the result is the sum

$$ \sum_{k=0}^{\infty} (-1)^k \log{\frac{k+1}{k+2}} $$

$$ = \lim_{n \rightarrow \infty} \; \log{\frac{\frac{1}{2} \frac{3}{4} \ldots \frac{2 n-1}{2 n}}{\frac{2}{3} \frac{5}{6} \ldots \frac{2 n+1}{2 n+2}}} $$

$$ = \log{\left ( \frac{2}{\pi} \right )} $$

share|cite|improve this answer
Seems reasonable. Thank you! – Martin Gales Jan 16 '13 at 16:27
Thank you for asking it - this was fun! – Ron Gordon Jan 16 '13 at 16:40
Yeah, math is about having fun! :-) (+1) – user 1618033 Jan 16 '13 at 16:54
To reverse the order of sum and integra, I understand that you appeal to the absolute convergence of sum and integral, that is, to the convergence of the positive series $\sum\limits_{k\geqslant0}\int\limits_0^{+\infty}(e^{-(k+1)y}-e^{-(k+2)y})dy/y$. But this series diverges. Maybe I did not understand the result you are applying, could you explain? – Did Jan 21 '13 at 9:17
Maybe we are speaking across each other. Look, do you agree that the sum in Line 2 absolutely converges (in this case, to $(1-e^{-y})^{-1})$? And that the integral absolutely converges (in this case, to $\log{\frac{k+1}{k+2}}$). Because each integral is also continuous, then we get a convergent result in exchanging the order of the sum and integral in Line 2. As I said, this does not apply to Line 3 because, as you point out, that the sum does not converge absolutely. But I am not seeking to reverse the order of integration here, just in Line 2. – Ron Gordon Jan 21 '13 at 14:38

I tried with "Differentiation under integration sign":

$$J(\alpha)=\int_0^1\frac{1-x^\alpha}{1+x}\frac{dx}{\ln x}\quad \alpha>0$$

Then, as usual, $$\frac{dJ}{d\alpha}=-\int_0^1\frac{x^\alpha}{1+x}dx=-f(\alpha),\text{(say)}$$

Then, integrating $$J(\alpha)=-\int f(\alpha)d\alpha+c$$ I used Mathematica to evaluate $f(\alpha)$ (it gives difference of two Harmonic numbers) and its integral. The integral is just $\ln\frac{\Gamma(\frac{2m+1}{2})}{\Gamma(\frac{m+1}{2})}$. Note that $J(0)=0$ and putting $\alpha=1$, the result follows.

share|cite|improve this answer
Very interesting approach! Thanks! – Martin Gales Jan 17 '13 at 16:05
Thanks, Martin! – Tapu Jan 17 '13 at 17:13
Where does $m$ come from in $\ln\dfrac{\Gamma(\frac{2m+1}{2})}{\Gamma(\frac{m+1}{2})}$? – Alex Schiff Aug 1 '14 at 14:33

Consider $$ \mathcal{I}(\alpha)=\int_0^1\frac{1-x^\alpha}{(1+x)\ln x}\ dx.\tag1 $$ Differentiating $(1)$ with respect $\alpha$ yields \begin{align} \frac{d\mathcal{I}}{d\alpha}&=\int_0^1\frac{\partial}{\partial\alpha}\left[\frac{1-x^\alpha}{(1+x)\ln x}\right]\ dx\\ &=-\int_0^1\frac{x^\alpha}{1+x}\ dx\\ &=-\int_0^1\sum_{k=0}^\infty(-1)^kx^{\alpha+k}\ dx\\ &=-\sum_{k=0}^\infty(-1)^k\int_0^1x^{\alpha+k}\ dx\\ &=-\sum_{k=0}^\infty\frac{(-1)^k}{\alpha+k+1}.\tag2 \end{align} Now consider polygamma function $$ \psi_n(z)=\frac{d^{n+1}}{dz^{n+1}}\ln\Gamma(z)\tag3 $$ and $$ \psi_n(z)=(-1)^{n+1}n!\sum_{k=0}^\infty\frac{1}{(z+k)^{n+1}}.\tag4 $$ Hence by using $(4)$ we obtain $$ \sum_{k=0}^\infty\frac{(-1)^{k}}{(z+k)^{n+1}}=\frac1{(-2)^{n+1}n!}\left[\psi_n\left(\frac{z}{2}\right)-\psi_n\left(\frac{z+1}{2}\right)\right].\tag5 $$ Using $(3)$ and $(5)$ then $(2)$ becomes \begin{align} \frac{d\mathcal{I}}{d\alpha}&=\frac12\left[\psi_0\left(\frac{\alpha+1}{2}\right)-\psi_0\left(\frac{\alpha+2}{2}\right)\right]\\ \mathcal{I}(\alpha)&=\frac12\int\left[\psi_0\left(\frac{\alpha+1}{2}\right)-\psi_0\left(\frac{\alpha+2}{2}\right)\right]\ d\alpha\\ &=\ln\Gamma\left(\frac{\alpha+1}{2}\right)-\ln\Gamma\left(\frac{\alpha+2}{2}\right)+C\\ &=\ln\Gamma\left(\frac{\alpha+1}{2}\right)-\ln\Gamma\left(\frac{\alpha+2}{2}\right)-\frac12\ln\pi,\tag6 \end{align} where $\mathcal{I}(0)=0$ and $C=-\ln\Gamma\left(\frac{1}{2}\right)$.

Thus \begin{align} \int_0^1\frac{1-x}{(1+x)\ln x}\ dx&=\mathcal{I}(1)\\ &=\ln\Gamma\left(1\right)-\ln\Gamma\left(\frac{3}{2}\right)-\frac12\ln\pi\\ &=\color{blue}{\ln\left(\frac{2}{\pi}\right)}. \end{align}

share|cite|improve this answer

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{I\equiv\int_{0}^{1}{1 - x \over 1 + x}\,{\dd x \over \ln\pars{x}}:\ {\large}}$

Lets consider $\ds{\fermi\pars{\mu}\equiv \int_{0}^{1}{1 - x^{\mu} \over 1 + x}\,{\dd x \over \ln\pars{x}}}$ such that $\ds{I = \fermi\pars{1}:\ {\large ?}}$. Note that $\ds{\fermi\pars{0} = 0}$.

Then, \begin{align} \fermi'\pars{\mu}&=-\int_{0}^{1}{x^{\mu} \over 1 + x}\,\dd x= \int_{0}^{1}{1 - x^{\mu} \over 1 + x}\,\dd x - \int_{0}^{1}{\dd x \over 1 + x} \\[3mm]&=\int_{0}^{1} \pars{1 - x^{\mu}}\pars{{1 \over 1 + x} + {1 \over 1 - x}}\,\dd x -\int_{0}^{1}{1 - x^{\mu} \over 1 - x}\,\dd x - \ln\pars{2} \\[3mm]&=2\int_{0}^{1}{1 - x^{\mu} \over 1 - x^{2}}\,\dd x -\int_{0}^{1}{1 - x^{\mu} \over 1 - x}\,\dd x - \ln\pars{2} \\[3mm]&=\int_{0}^{1}{x^{-1/2} - x^{\pars{\mu - 1}/2} \over 1 - x}\,\dd x -\int_{0}^{1}{1 - x^{\mu} \over 1 - x}\,\dd x - \ln\pars{2} \\[3mm]&=\int_{0}^{1}{1 - x^{\pars{\mu -1}/2} \over 1 - x}\,\dd x -\int_{0}^{1}{1 - x^{-1/2} \over 1 - x}\,\dd x -\int_{0}^{1}{1 - x^{\mu} \over 1 - x}\,\dd x - \ln\pars{2} \end{align}

$$ \fermi'\pars{\mu}=\Psi\pars{\mu + 1 \over 2} -\Psi\pars{\mu + 1} + \ln\pars{2} $$ where we used the Digamma $\ds{\Psi\pars{z}}$ identity $\ds{\bf\mbox{6.3.22}}$ and the identity $\ds{\bf\mbox{6.3.3}}$.

Since $\ds{\Psi\pars{z} = \totald{\ln\pars{\Gamma\pars{z}}}{z}}$ and $\ds{\fermi\pars{0} = 0}$: $$ \fermi\pars{\mu} =\ln\pars{{2^{\mu}\,\Gamma^{2}\pars{\bracks{\mu + 1}/2} \over \Gamma\pars{\mu + 1}}\, {\Gamma\pars{1} \over 2^{0}\,\Gamma^{2}\pars{1/2}}} =\ln\pars{{2^{\mu} \over \pi}\, {\Gamma^{2}\pars{\bracks{\mu + 1}/2} \over \Gamma\pars{\mu + 1}}} $$ with the identities $\quad\ds{\Gamma\pars{1} = 1\quad\mbox{and}\quad\Gamma\pars{\half} = \root{\pi}}$.

With $\ds{\Gamma\pars{2} = 1}$: $$ I=\color{#66f}{\large\int_{0}^{1}{1 - x \over 1 + x}\,{\dd x \over \ln\pars{x}}}= \fermi\pars{1} = \color{#66f}{\large\ln\pars{2 \over \pi}} \approx {\tt -0.4515} $$

share|cite|improve this answer

You may like this method. Note $$ \int_0^1x^ada=-\frac{1-x}{\ln x}, \text{ for }x>0, H_a=\sum_{k=1}^\infty\frac{a}{k(a+k)}, $$ and hence \begin{eqnarray} \int_0^1\frac{1-x}{1+x}\frac{dx}{\ln x}&=&-\int_0^1\int_0^1\frac{x^a}{1+x}dadx\\ &=&-\int_0^1\int_0^1\frac{x^a}{1+x}dxda\\ &=&-\frac{1}{2}\int_0^1(H_{\frac{a}{2}}-H_{\frac{a-1}{2}})da\\ &=&-\frac{1}{2}\int_0^1\sum_{k=1}^\infty\left(\frac{a}{k(a+2k)}-\frac{a-1}{k(a+2k-1)}\right)da\\ &=&-\frac{1}{2}\sum_{k=1}^\infty\left(4\ln k-2\ln(k^2-\frac{1}{4})\right)\\ &=&-\frac{1}{2}\ln\prod_{k=1}^\infty\frac{k^4}{(k^2-\frac{1}{4})^2}\\ &=&-\prod_{k=1}^\infty\frac{k^2}{k^2-\frac{1}{4}}\\ &=&-\ln\left(\frac{\pi}{2}\right). \end{eqnarray} In the last step, we used the Wallis Formula from here.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.